Demografia nos municípios paranaenses - análise dos censos 1991 a 2022 - Ricardo Rodrigues Monteiro; Luiz Fernando de Carli Lautert (Confins)
The article presents a series of twelve maps made with data from the 1990, 2000, 2010 and 2022 Censuses, which visualize general information on population variation and the percentages of age groups in Paraná's municipalities.